Market assessment approaches for adoption of porcine cystycercosis vaccine in Uganda - CGIAR Research Program on Livestock (2018)
GALVmed - Public Private Partnership is promoting a combined cysticercosis vaccine and treatment. The flagship research found that a purely market-based approach was unlikely to succeed and recommended other strategies.